2008
DOI: 10.1007/s11250-008-9133-6
|View full text |Cite
|
Sign up to set email alerts
|

Bodyweight and carcass characteristics of somali goats fed hay supplemented with graded levels of peanut cake and wheat bran mixture

Abstract: The experiment was conducted for ninety days of feeding trial at Haramaya University, Ethiopia using twenty four yearling male Somali goats weighing 20.4 +/- 2.02 (mean +/- SD) with the objectives to evaluate the effect of supplementation of peanut cake and wheat bran mixture (3:1) on body weight (BW) gain and carcass characteristics of Somali goats. The experiment was arranged with six blocks and four treatments in a randomized complete block design. The treatments were ad libitum feeding of hay (T1, control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
10
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
8
10
3
Order By: Relevance
“…For instance, in fine wheat feed, the CP content is generally within the range of 16-21%, and the coarse wheat feed or bran usually contains less CP. The CP content of the hay used in the experiment was found to be in agreement with the 3-7% CP reported for hay prepared from grass in different studies (Bishaw and Melaku 2008;Nega and Melaku 2009;Melaku and Betsha 2008). According to Van Soest (1994), feeds with CP contents falling in this range constrain rumen function.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…For instance, in fine wheat feed, the CP content is generally within the range of 16-21%, and the coarse wheat feed or bran usually contains less CP. The CP content of the hay used in the experiment was found to be in agreement with the 3-7% CP reported for hay prepared from grass in different studies (Bishaw and Melaku 2008;Nega and Melaku 2009;Melaku and Betsha 2008). According to Van Soest (1994), feeds with CP contents falling in this range constrain rumen function.…”
Section: Discussionsupporting
confidence: 83%
“…Comparable amount of hay DM intake as observed in this study was reported for Somali goats (Melaku and Betsha 2008) and Farta sheep (Nega and Melaku 2009) fed hay without supplementation. The decrease in natural pasture hay intake due to supplementation with LSC, WB, and their mixtures at different proportions may be attributed to the substitution effect of the concentrate supplements.…”
Section: Feed Intakesupporting
confidence: 71%
See 1 more Smart Citation
“…As expected, the carcass yield improved with increasing slaughter weight, and this agrees with reports on Boer or their crossbreds (Ryan et al 2007) and also on other tropical goats (Attah et al 2004;Mahgoub et al 2005;Phengvichith and Ledin 2007;Melaku and Betsha 2008). The present carcass yield of Creole (mean of 53.5%) fell within the upper range of the cited papers.…”
Section: Carcass Conformationsupporting
confidence: 92%
“…The fi nding of the current study is in agreement with Feyera and Animut (2011). Similar result were also reported by Simret (2005), Gebru (2009) andFeyera andAnimut (2011).…”
Section: As Illustrated Insupporting
confidence: 92%